Comparison of the Photofunctionalization and Platelet-Rich Plasma in the Immediate Implants - R Padmini Rani; Harisha Dewan; Ahmed Abed; Aheli Pal; Arshad Idrisi; Mohammed Ziauddeen Mustafa; Sirisha Kommuri (Wolters Kluwer Medknow Publications, 2024)
Introduction: Many adjuvant methods have been researched to enhance the immediate implant success in the recent times. The study's goal was to compare the aesthetic and biological results of immediate dental implants in the aesthetic zone to standard tapered root form implants that had not undergone pre-treatment with platelet-rich plasma or photofunctionalization. Materials and Methods: The study used a randomized controlled trial as its design. Ninety subjects were chosen at random and placed into three groups: a control group, a case group, and a group that needed replacement of their maxillary anterior teeth right away following extraction. The interventional groups received the "Platelet-Rich Plasma (PRP)" or "Photofunctionalization (PF)" group before the implant placement. After the delayed loading approach, the prosthesis was given after 6 months. At the second and fourth weeks, as well as 2, 4, 6, and 12 months (P 0.05), follow-up was conducted. The success and survival rate, aesthetic, and biological outcomes were assessed. One-way ANOVA was used to compare outcomes, and repeated-measures ANOVA was used to assess intragroup variations over baseline and follow-up. Results: The distal, mesial, and mean marginal bone loss as well as the aesthetic scores for pink and white did not differ significantly between groups. The implant stability however was significantly higher in the PF and PRP groups as compared to the controls. A single implant failed in all the three groups. The success percentage was similar for all the groups. Conclusion: The stability of immediate dental implants pre-treated with PRP or PF differed statistically significantly than the subjects in the control group, while other parameters remained the similar between the groups.